Thymomas With Intravascular and Intracardiac Growth - Arrossi, Andrea Valeria; Dermawan, Josephine K.; Bolen, Michael; Raymond, Daniel (Frontiers in Oncology, 2022)
Thymomas are derived from the epithelial component of the thymus and constitute the most common tumor of the anterior mediastinum. These neoplasms are considered malignant for their potential for invasion and metastases. Several histopathologic subclassification schemes have been proposed over the years, however, correlation of histotypes with prognosis remains controversial. In contrast, studies invariably have shown that staging and resection status correlate with oncologic behavior and disease outcomes. In this regard, several staging systems have been presented, though transcapsular invasion and degree of involvement of adjacent anatomic structures are common denominators of all schemes. Involvement of the great vessels and heart most commonly results from direct invasion, which may lead to unusual clinical presentations such as superior vena cava syndrome. Moreover, intravascular and intracardiac growth with or without direct mural invasion rarely occurs. We provide an overview of thymomas with intravascular and intracardiac involvement.